2015
DOI: 10.1042/bst20150028
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the 18-kDa translocator protein: recent perspectives for neuroprotection

Abstract: The translocator protein (TSPO, 18 kDa), mainly localized in the outer mitochondrial membrane of steroidogenic tissues, is involved in several cellular functions. TSPO level alterations have been reported in a number of human disorders, particularly in cancer, psychiatric and neurological diseases. In the central nervous system (CNS), TSPO is usually expressed in glial cells, but also in some neuronal cell types. Interestingly, the expression of TSPO on glial cells rises after brain injury and increased TSPO e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…These antagonistic expectancies regarding properties of TSPO and its ligands potentially may lead to widely divergent discrepancies in research approaches and interpretations of results. Another confounding aspect does relate to the now well appreciated concept that TSPO has homeostatic functions [20,23,26,38,62,63,70,71]. Assuming this to be true, many of the seemingly contradictory results can be explained as upregulatory and downregulatory characteristics of this potential homeostatic apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These antagonistic expectancies regarding properties of TSPO and its ligands potentially may lead to widely divergent discrepancies in research approaches and interpretations of results. Another confounding aspect does relate to the now well appreciated concept that TSPO has homeostatic functions [20,23,26,38,62,63,70,71]. Assuming this to be true, many of the seemingly contradictory results can be explained as upregulatory and downregulatory characteristics of this potential homeostatic apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well recognized that TSPO presents a target that can be utilized for treatment of various diseases. In particular its characteristic as a receptor make it per definition a target for the development of ligands designed cure such diseases [22,45,71,73]. …”
Section: Discussionmentioning
confidence: 99%
“…To this aim, kinetic experiments were performed to measure k on and k off rate constants for each compound at [ 3 H]2 binding site, and their RT was calculated. [29] As should be notedf rom the data reported in Ta ble1,t he majority of the tested compounds were found to be rapid dissociating competitorsoft he binding site of 2 (i.e., 3,4,5,7,9,12 and the reference 1). (14).…”
Section: Nct00502515)mentioning
confidence: 99%
“…Numerous TSPO ligands are able to potently and dose‐dependently stimulate steroid biosynthesis in steroidogenic cells, and they have been proposed as innovative therapeutic tools in several pathological conditions, due to their neuroprotective, anxiolytic, anti‐inflammatory, and regenerating properties in different in vitro and in vivo models . To date, phase II clinical trials have been concluded for the treatment of diabetic peripheral neuropathy (ClinicalTrials.gov identifier: NCT00502515), and generalized anxiety disorder (NCT00108836) …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation